Crystal Plasticity Finite Element Analysis of Spherical Nanoindentation Stress–Strain Curve of Single-Crystal Copper - Haoming Xia; Zhanfeng Wang; Shichao Qu; Weijie Shan; Rongkai Tan (Crystals)
In this paper, we perform crystal plasticity finite element (CPFE) simulations of spherical nanoindentation to extract the indentation stress–strain (ISS) curve for a single-crystalline copper. The load–displacement curves on the Cu (010) surface at incremental indentation depths are obtained. Surface pile-up topography is explored and characterized by the activated slip systems on the indented surface and stress distribution on the cross-section to reveal the crystal anisotropy. And the effect of indentation depth on the stiffness and surface pile-up height is further analyzed. Finally, the zero point is defined, and the indentation stress–strain (ISS) curve is extracted from load–displacement curves. The validity of the ISS curve is demonstrated for crystalline copper materials by comparing measured results published in the literature.